PRIORITY AREAS OF THE GREEN ECONOMY IN SUSTAINABLE ECONOMIC DEVELOPMENT - Ibragimova Saodat Abdumuminovna (American Journals, 2024)
At the new stage of development of our country, as in all other areas, work being carried out in the field of environmental protection, rational use of natural resources, and prevention of the negative impact of environmental problems on human health is key to sustainable development.
Keywords: Green economy, economic development, the concept of